Characterization and selection of probiotic lactic acid bacteria from different dietary sources for development of functional foods - Khushboo,; Karnwal, Arun; Malik, Tabarak (Frontiers in Microbiology, 2023)
In this current study, the lactic acid bacteria (LAB) were isolated from several dietary sources such as curd, pickle, milk, and wheat dough. The principal focus of this study was to determine the survivability of these microorganisms in the gastrointestinal tract and to use promising strains to create probiotic drinks with numerous health benefits. The isolates were identified using a combination of morphological, biochemical, molecular and sugar fermentation patterns, like phenotypic characteristics, sugar fermentation, MR-VP reaction, catalase test, urease test, oxidase test, H2S production, NH3 production synthesis from arginine, citrate utilization, indole test, and 16s rRNA sequencing. Two (CM1 and OS1) of the 60 isolates obtained showed the best probiotic results and were identified as Lactobacillus acidophilus CM1 and Lactobacillus delbrueckii OS1. These organism sequences were submitted to Gen bank with accession numbers OP811266.1 and OP824643.1, respectively. The acid tolerance test results indicated that most strains could significantly survive in an acidic environment with pH levels of 2 and 3. Similarly, the salt tolerance test results showed that both Lactobacillus acidophilus CM1 and Lactobacillus delbrueckii OS1 could survive at 4 and 6% NaCl levels significantly. The isolates also showed their ability to ferment sugars such as lactose xylose, glucose, sucrose, fructose. In conclusion, the study showed that the bacteria isolated from different food sources were indeed probiotic lactic acid bacteria and had probiotic properties. These isolates hold potential for future research in the formulation of millet-based probiotic beverages. However, further studies are required to confirm their effectiveness and safety in improving human health. This research provides a foundation for developing functional foods and drinks that can positively affect human health by incorporating probiotic microorganisms.